أسلوب بيز في تحليل البيانات غير التامة - كاظم اموري هادي; نايف قتيبة نبيل (Journal of Economics and Administrative Sciences, 2008)
In this paper we will explain ,how use Bayesian procedure in analysis multiple linear regression model with missing data in variables X’s as the new method suggest , and explain some of missing Patterns under missing mechanism , missing complete at random MCAR and compare Bayesian estimator with complete case estimator by use simulation procedure .